Reduction of Jacobi-Nijenhuis manifolds - Costa, J. M. Nunes da (2001)
A reduction theorem for Jacobi-Nijenhuis manifolds is established and its relation with the reduction of homogeneous Poisson-Nijenhuis structures is shown. Reduction under Lie group actions is also studied